POLITIK HUKUM ISLAM DAN MAQASID AL-SYARIAH - Miskari Miskari (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2019)
Abstrack: This study will discuss the Politics of Islamic law and maqashid sharia, where both meet at the same point, namely the benefit of the nation and the state and its people both in the world and in the hereafter. In order to realize the Islamic values of Islamic legal politics into real life, fukaha (Islamic law experts) launched a theory, among others, maqashid syari'ah (the objectives of Islamic law). The Maqashid Shari'ah aspect divides three complementary priority scales. First, dharury, as a necessity or necessity, is something that must exist for the sake of human life. If something doesn't exist, then human life will definitely be destroyed. The goals of the daruri are to save religion, soul, reason, property, descent and self-esteem (hurdles, pride or honor). For example, to save lives, the Qur'an instructs humans to eat, but they cannot overdo it. Second, Hajy, or needs, meaning, something is needed for the survival of human life. If something does not exist, then human life will not experience destruction, but difficulties will confront. Third, tahsiny, or decorative-ornamental processes. That is, the absence of decorative-ornamental matters will not destroy the purpose of dharury.Keyword: Politics; Islamic Law; Maqashid Syariah